Factors Affecting the Adoption of Renewable Energy (Solar) in Rhodes Park Area of Lusaka District, Zambia - Kumar, Narayana Bharath; Sikalumbi, Dewin Arona (Journal of Climate Policy, 2025)
Purpose: This study investigated the factors affecting the adoption of solar energy in Rhodes Park, Lusaka. The objectives of the study were to assess the awareness of solar energy benefit among residents and business, also to identify the challenges to adoption and to evaluate the effectives of existing incentives and policies. Methodology: A mixed methods approach was used, with qualitative and quantitative data. A total of 240 respondents took part in the quantitative part through a questionnaire, while 12 respondents took part in the qualitative part through interviews. Findings: The findings revealed that 75 percent of the respondents were aware of the benefits of solar energy, from this adoption was observed to be low due to financial constraints, lack of information as well as concerns about efficiency. The high upfront cost was recognized as the most significant barrier according to 63 percent of the respondents, it was followed limited awareness on government incentives. In addition to that social media and traditional media were the primary sources of information, yet government policy communication hindered adoption. To support these findings, they aligned with the Barrier theory, which explains the disconnect between awareness and actual implementation due to economic and informational challenges. Unique Contribution to Theory, Policy and Practice: The study concluded that while awareness levels were higher, inadequate policy communication, financial problems and maintenance costs prevented the adoption. The study recommended that there is a need for financial support through subsidies and loans as well as technical education or training to address these challenges. This requires policy direction to guide the suppliers and beneficiaries of solar energy.